Freight Transport for Development Toolkit : Integrated Logistics Services - Kopicki, Ron (World Bank, Washington, DC, 2017)
Globalization has imposed entry requirements on developing economies. Countries need to have the ability to synchronize the business processes which take place within local producers with business processes, which take place in the supply chains of their suppliers and their customers. Integrated logistics services are nowadays a critical component of international freight transport systems, but their development and coverage vary widely across countries, in particular in the developing world. This paper explains this important development. It documents the increasingly important role, which third party logistics service providers play in facilitating business process connectivity and thus in integrating producers based in developing countries into the global economy. It provides a look at the global significance of integrated logistics services in a globalized economy, and goes on to review specific examples of establishment of such services in developing countries. These examples in turn suggest a set of specific policy recommendations to help policymakers enable the development of efficient logistics services to serve both their domestic and international markets. The paper describes ways in which integrated logistics services have evolved over the past 20 years. It describes aspects of that development, which have particular significance for accelerating the economic growth of developing economies. From a review of various means, which third party service providers have used to integrate the business processes of their clients into the supply chains of their clients, it attempts to develop some general principles, which can help policy makers to enhance the competitiveness of their own economies. In additional it discusses the interface between public and private sectors and particular ways in which public policy can enhance competitiveness through this important growth leverage. It goes on to discuss appropriate means and modes for regulating an emerging third party logistics industry and, finally, it suggesting specific initiatives and service design initiatives, which can help, accelerate economic development.